Development of an Inertial Linear Ultrasonic Motor with a Double-Stator Structure Based on Bending Mode - Lin Yang; Yue Xiong; Xinwei Hong; Jiaquan Wen; Jie Zhang; Rongcheng Zhao (Applied Sciences)
An inertial linear ultrasonic motor with a novel double-stator structure is proposed for achieving higher performance and resolution in this paper. Utilizing a symmetrical structure and single sawtooth wave signal, the prototype is capable of outputting effective linear motion based on inertial movement. The validity and rationality of the prototype are investigated by conducting finite element analyses. The experimental setups are built up to acquire the output characteristics of the motor. The experimental results indicate that the motor can achieve a maximum output velocity of 8.746 mm/s and thrust force of 1.645 N, which is almost twice the output performance of a motor with a single stator. The displacement solution of the motor can be adjusted by changing the amplitude of the voltage, with a resolution of 27 nm. Simultaneously, the relationships between the output characteristics and the input parameters are measured and analyzed during the experiments. Compared to the actuators with complex structures and multi-signal drives, the proposed motor exhibits the merits of higher output performance with the double-stator structure, providing an alternative direction for the further development of the inertial linear ultrasonic motor.